Cytotoxin-Associated Gene A-Positive Helicobacter pylori Promotes Autophagy in Colon Cancer Cells by Inhibiting miR-125b-5p - Xiaolin Zhong; Ou Chen; TieJun Zhou; Muhan Lü; Juyi Wan (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objectives. To investigate the effects of cytotoxin-associated gene A- (CagA-) positive Helicobacter pylori on proliferation, invasion, autophagy, and expression of miR-125b-5p in colon cancer cells. Methods. Colon cancer cells were cocultured with H. pylori (CagA+) to analyze the effects of H. pylori on miR-125b-5p and autophagy. Colon cancer cells infected with H. pylori (CagA+) were mimicked by transfection of CagA plasmid. The effects of CagA on the proliferation, invasion, and autophagy of colon cancer cells were analyzed. Cell counting kit-8 (CCK-8), clone formation, and Transwell assays were used to detect cell viability, proliferation, and invasion ability, respectively. Proteins and miRNAs were detected by western blotting and qPCR, respectively. Results. H. pylori (CagA+) inhibited expression of miR-125b-5p and promoted autophagy in colon cancer cells. MiR-125 b-5p was underexpressed in colon cancer cells after CagA overexpression. CagA promoted colon cancer cell proliferation, invasion, and autophagy. Overexpression of miR-125b-5p inhibited the proliferation, invasion, and autophagy of colon cancer cells and reversed the effects of CagA. Conclusion. H. pylori (CagA+) infection may promote the development and invasion of colon cancer by inhibiting miR-125b-5p.